CAN WE ABANDON A TRADITIONAL IRRIGATION IN THE OUAKDA OASIS (ALGERIA)? - Remini, Boualem; Rezzoug, Cherif (GeoScience Engineering, 2018)
Can we abandon traditional irrigation to the detriment of modern irrigation in the oasis of Ouakda? Is the question we posed in this study. Indeed, based on three missions carried out in the oasis of Ouakda during the years 2013, 2014 and 2015, we made visits and investigations to ancestral works as well as surveys of the local population. The results indicate that the Ksourian population irrigated the gardens and the palm grove by surface and underground water. Two ancestral dams made on the wadi Bechar for irrigation the gardens of the lower part. On the other hand, the foggaras irrigated the upper part of the palm grove. Today, new land has been built on the upper part of the palm grove. Thanks to new hydraulic techniques such as drilling and motor pumps, modern agriculture has developed on the other side of the palm grove to the detriment of oasis agriculture. Keywords: Algeria, Oasis, Ouakda, Foggara, Irrigation, Agriculture https://doi.org/10.2478/gse-2018-0004